Laparoscopic fenestration surgery of a large primary splenic cyst - Bhomaj, Harsh; Padhy, Aditya Prasad; Pujari, Pran Singh (International Surgery Journal, 2020)
Splenomegaly is a major and perhaps the only concern pertaining to spleen for surgeons. Splenic cysts are rare presentations as splenomegaly, with about 800 cases reported so far. Presenting a case report of a 19 years old boy presented with a mass in the abdomen below the rib cage on the left side since 1 year. No other associated complaints. On clinical evaluation a soft cystic mass of size 10×10 cm approximately, was felt extending upto and just above the umbilicus, occupying the left hypochondrium, epigastrium, left lumbar and part of umbilical region. On contrast enhanced computed tomography (CECT) abdomen and pelvis, a well-defined, rounded cystic swelling arising from the spleen and abutting the surrounding structures was noted. Clinically diagnosing it as a primary splenic cyst and after thorough preoperative evaluation the patient was planned for laparoscopic fenestration surgery of the cyst. Surgery involved aspirating, deroofing of the cyst with omental packing of the cyst cavity. This surgery is a novel minimally invasive spleen preserving approach to such types of splenic cysts. This approach carries the least morbidity and recurrence rate among its other options.